Factors influencing the demulsification time of asphalt emulsion in fresh cement emulsified asphalt composite binder. Issue 2 (1st February 2022) - Liu, Baoju; Shi, Jinyan; He, Yitian; Yang, Yuanxia; Jiang, Junyi; He, Zhihai
Abstract : Emulsified asphalt as an indispensable raw material for high-speed railway ballastless slab track and pavement structure is subjected to different combinations of material and construction parameters leading to uncontrollable demulsification time. By examining the demulsification time of cationic emulsified asphalt mixed with cement or cement and sand, the factors influencing the demulsification time of emulsified asphalt were studied. The increase of pH value is detrimental to the hydration of cement, and it is beneficial to prolonging the demulsification time. The incorporation of the stabilisers (Polyvinyl acetate, sodium carboxymethylcellulose, CaCl2 and NH4 Cl), either increasing the viscosity of the fresh cement emulsified asphalt composite binder or changing the electric double layer on the surface of asphalt particles, this is detrimental to prolonging the demulsification time of emulsified asphalt mixed with cement. The increase of the stirring speed can shorten the demulsification time of emulsified asphalt. Meanwhile, increasing of additional water can dilute cement and asphalt particles, and prolong the demulsification time. Conversely, an increase amount of cement will lead to an increase in the amount of water used for wrapping and hydration, and shortening of demulsification time Meanwhile, with the treatment time prolonging, the demulsification speed of the asphalt emulsion increases. In addition, the demulsification process of emulsified asphalt in cement emulsified asphalt mortar actually is a process of asphalt re-aggregation observed by the optical microscope.